The Influence of Accounting Information System and Energy Consumption on Carbon Emission in the Textile Industry of Indonesia: Mediating Role of the Supply Chain Process - Dalle, Juhriyansyah; Hayat, Atma; Karim, A.; Tirtayasa, Satria; Sulasmi, Emilda; Prasetia, Indra (International Journal of Energy Economics and Policy, 2020)
The purpose related to the current article is to investigate the impact of accounting information system (AIS) and structure of energy consumption on the carbon emission of the textile industry in Indonesia. The aim also consist upon the investigation of mediating impact of supply chain process on the links of AIS and CO2 emission, structure of energy consumption and CO2 emission. The employees related to the AIS and environment sustainability are the respondent who provide the data through questionnaires that were evaluated by the help of PLS-SEM. The results show that AIS and structure of energy consumption have positive nexus with the carbon emission of the textile industry in Indonesia. The results are show that supply chain process has positive mediation among the links of AIS and CO2 emission, structure of energy consumption and CO2 emission. The regulation developing authorities and new researchers are the users of this article who gel help while preparing the policies and also in the exploration of this area in the future. Keywords: Accounting Information System, Carbon Emission, Structure of Energy Consumption, Supply Chain Process JEL Classifications: Q19, E59 DOI: https://doi.org/10.32479/ijeep.10693